Elemen Tawhidik Dalam Perbincangan Ilmu Geometri Karya Tokoh Islam: Analisis Terhadap Kitab al-Hiyal oleh al-Farabi : Tawhidic Elements in the Geometric Discussion by Islamic Scientist: An Analysis on al-Hiyal’s Book by al-Farabi - Ishak, Shahrul Nizam; Hassan Mydin, Shaik Abdullah (Journal of Al-Tamaddun, 2025)
There is a peculiarity among scholars in the present day when the field of geometry is linked to al-Farabi (d. 950M/339H)and even some Western scientists are also failing to acknowledge the relationship between the two. Nevertheless, Ibn Abi Usaybi‘ah (m. 1270M/668H) characterized al-Farabi as a smart individual proficient in mathematical sciences, while Seyyed Hossein Nasr (1933M/1351H-present) referred to him as a Muslim philosopher-scientist. Hence, this paper aims to highlight and elucidate al-Farabi’s geometrical treatise, al-Hiyal al-Ruhaniyyah Wa al-Asrar al-Tabi‘iyyah Fi Daqa’iq al-Asykal al-Handasiyyah (al-Hiyal), by examining the tawhidic elements within his discourse. The focus of the discussion of the book is on the construction algorithm of various geometric shapes based on lines and surfaces. However, this study’s completion relies on a qualitative methodology that uses content analysis as its foundation. The research findings indicate that the organization of themes inside the chapters is distinctly aligned with the complexity levels of geometric form production. The author’s notes succinctly and eloquently articulate details such the title designation, the rationale for writing, the uniqueness of the composition, the classification of al-Sina‘at al-Handasiyyah, the completion date and praises for the divine essence. Elements of tawhidic associations can be traced through four words, namely Basmalah, al-Jalalah, Solawah and InsyaAllah, which are found in his discussion. Therefore, emphasizing the book al-Hiyal by al-Farabi, particularly its discourse on tawhidic, would be advantageous in fostering interest among students in contemporary studies related to geometric science, as the foundation of every new civilization is built upon the accomplishments of preceding societies.